Evaluation of the coordination preferences and catalytic pathways of heteroaxial cobalt oximes towards hydrogen generation. Issue 5 (12th February 2016) - Basu, Debashis; Mazumder, Shivnath; Niklas, Jens; Baydoun, Habib; Wanniarachchi, Dakshika; Shi, Xuetao; Staples, Richard J.; Poluektov, Oleg; Schlegel, H. Bernhard; Verani, Cláudio N.
Abstract : A mechanistic investigation of the changes associated with distinct oxidation states of cobalt oximes and relevant for catalytic hydrogen generation. Abstract : Three new heteroaxial cobalt oxime catalysts, namely [Co III (prdioxH)( 4 t Bu py)(Cl)]PF6 (1 ), [Co III (prdioxH)( 4Pyr py)(Cl)]PF6 (2 ), and [Co III (prdioxH)( 4Bz py)(Cl)]PF6 (3 ) have been studied. These species contain chloro and substituted tert -butyl/pyrrolidine/benzoyl-pyridino ligands axially coordinated to a trivalent cobalt ion bound to the N4 -oxime macrocycle (2 E, 2′ E, 3 E, 3′ E )-3, 3′-(propane-1, 3-diylbis(azanylylidene))bis(butan-2-one)dioxime, abbreviated (prdioxH) − in its monoprotonated form. Emphasis was given to the spectroscopic investigation of the coordination preferences and spin configurations among the different 3d 6 Co III, 3d 7 Co II, and 3d 8 Co I oxidation states of the metal, and to the catalytic proton reduction with an evaluation of the pathways for the generation of H2 via Co III –H − or Co II –H − intermediates by mono and bimetallic routes. The strong field imposed by the (prdioxH) − ligand precludes the existence of high-spin configurations, and 6-coordinate geometry is favored by the LS Co III species. Species1 and3 show a split Co III /Co II electrochemical wave associated with partial chemical conversion to a [Co III (prdioxH)Cl2 ] species, whereas2 shows a single event. The reduction of these Co III complexes yields LS Co II and LS Co I species in which the pyridine acts as the dominant axial ligand. In the presence of protons, the catalytically active Co I species generates a Co III –H − hydride species that reacts heterolytically with another proton to generate dihydrogen. The intermediacy of a trifluoroacetate-bound Co III /Co II couple in the catalytic mechanism is proposed. These results allow for a generalization of the behavior of heteroaxial cobalt macrocycles and serve as guidelines for the development of new catalysts based on macrocyclic frameworks.